Healthcare workers’ vaccination at European and Italian level: a narrative review: Updates of vaccination coverages of HCWs - Squeri, Raffaele; Di Pietro, Angela; La Fauci, Vincenza; Genovese, Cristina (Acta Biomedica Atenei Parmensis, 2019)
Today some vaccine-preventable diseases remain an important cause of morbidity and mortality worldwide despite the availability of new vaccines. Healthcare workers are particularly at risk to acquire an infection disease, playing a fundamental role in nosocomial transmission, which makes them an important target group for vaccination. The vaccination recommendations of HCWs, as well as the general population, differ from country to country. Furthermore, coverage rates vary widely a lot over the world, making HCWs vulnerable to disease and so healthcare settings to outbreaks. The motivations of vaccine hesitancy are many and maybe other studies would help policymakers and stake-holders to shape programs to improve vaccination coverage and the control of infectious diseases through the correct application of guidelines on prevention.